Different radiologic procedures to evaluate the success of Pleurodesis in patients with malignant pleural effusion - Mohamed S. Sadek; Tarek S. Essawy; Elsayed A. Taha; Marwa E. Elnaggar (Egyptian Journal of Chest Disease and Tuberculosis)
Background To treat symptoms brought on by a large, recurring malignant pleural effusion, chemical pleurodesis is recommended. Before pleurodesis, a drain is left in the pleural space until the pleural fluid collection stops. As little as 50 ml of pleural fluid can be found using chest ultrasonography, which can also verify the pleural surfaces’ conjunction, a sign of successful pleurodesis. Patients and methods Thirty patients with malignant pleural effusion had intercostal tube insertion as part of this interventional trial. Before the sclerosing drug was injected, transthoracic ultrasonography was used to evaluate each case to see whether the sliding sign was present. A month later, a follow-up transthoracic ultrasound was performed to evaluate the sliding sign, which indicates whether the pleurodesis was successful or not. Results The mean age of participants was 60 ± 12 years, with slightly more males (53.3%, n=16) than females (46.7%, n=14). Two-thirds (66.7%) reported chest pain, while half of the patients (50%) had complained of cough. The majority (76.7%, n=23) presented with pleural nodules. Every participant (100%) demonstrated the presence of both effusion and collapse in the computed tomography images. Most of the cases (63.3%, n=19) were treated with bleomycin during pleurodesis. All patients (100%) demonstrated the presence of the sliding sign before pleurodesis with significant absence after the procedure (P<0.001). 24 out of the 30 (80%) patients experienced successful outcomes. Conclusions Because thoracic ultrasonography may identify the lack of pleural sliding, it can be used to evaluate the success of pleurodesis. Furthermore, the results of pleurodesis were further confirmed by computed tomography scans and chest radiography, which completed the assessment by indicating the presence or absence of effusion and collapse.